Clear cell odontogenic carcinoma of the mandible: a treatment strategy - Ferreira, Sabrina [UNESP]; Faverani, Leonardo Perez [UNESP]; Santos, Gabriel Mulinari dos [UNESP]; Martins, Everton Pontes; Garcia Júnior, Idelmo Rangel [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2018)
Clear cell odontogenic carcinoma (CCOC) is a rare odontogenic tumor of the jaws, histologically characterized by the presence of agglomerates of cells with eosinophilic cytoplasm. The patient, a 62-year-old Caucasian woman, presented an intraosseous lesion in the mandibular symphysis. A clinical examination revealed a discrete volumetric increase with a hard consistency, palpable to extraoral and intraoral examinations. Imaging studies revealed an extensive radiolucent area, without defined limits, extending from the region of the right second premolar to the left canine. Incisional biopsy analysis indicated a diagnosis of CCOC. The treatment proposed was segmental resection of the mandible with a safety margin. After six months without recurrence, definitive mandibular reconstruction was performed using an iliac crest graft, followed by rehabilitation with implant-supported denture after five months. After three years of post-resection follow-up, the patient has shown no evidence of recurrence or metastasis. She continues to be under follow-up. To conclude, CCOC must be considered a malignant tumor with aggressive behavior. Previous studies have shown that resection with free margins is a treatment with a lower rate of recurrence. Nevertheless, long-term follow-up is necessary for such patients.
Keywords: Odontogenic carcinoma; Clear cell; Mandible